The rights of older persons. Social participation as an essential dimension of active aging - Pérez Jaraba, Mª Dolores (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2026)
Today, older adults are a group that faces multiple forms of discrimination. Their freedom to make decisions about their own lives, as well as their rights to participate in work,  education, and politics, are not adequately protected. Although some regulations have been developed to safeguard and promote the active participation of older adults, these measures have proven to be insufficient and fragmented. This highlights the need for a comprehensive approach that includes more targeted public policies and legislation, along with a stronger commitment from society as a whole.
Keywords: older people; human right; active aging; social participation